Upregulating MicroRNA-410 or Downregulating Wnt-11 Increases Osteoblasts and Reduces Osteoclasts to Alleviate Osteonecrosis of the Femoral Head - Yukun Yin; Lixiang Ding; Yu Hou; Haoran Jiang; Ji Zhang; Zhong Dai; Genai Zhang (Nanoscale Research Letters, 2019)
Abstract Background Little is known regarding the functional role of microRNA-410 (miR-410) in osteonecrosis of the femoral head (ONFH); hence, the aim of the present study was to investigate miR-410 targeting Wnt-11 to modulate the osteogenic and osteoclastic mechanism in the prevention of ONFH. Methods Fifteen ONFH samples and 15 normal samples were gathered. The pathological changes of the femoral head, osteoblasts, and osteoclasts in the clinical samples were observed. The rat model of ONFH was injected with agomir-miR-410, Wnt-11-siRNA, or oe-Wnt-11. MiR-410; Wnt-11; osteoblast-related factors alkaline phosphatase (ALP), bone gamma-carboxyglutamate protein (BGLAP), and Collα1 expression; and osteoclast-related factors acid phosphatase 5 (ACP5), cathepsin K (CTSK), and MMP9, as well as Bcl-2 and Bax expression, were tested by RT-qPCR and western blot analysis. The osteogenic function index ALP and OCN together with osteoclast function index NTX-1 and CTX-1 in serum was tested by ELISA. Results MiR-410, ALP, BGLAP, and Collα1 degraded as well as Wnt-11, ACP5, CTSK, and MMP9 enhanced in ONFH tissues of the clinical samples. Upregulated miR-410 and downregulated Wnt-11 enhanced bone mineral density (BMD) and BV/TV of rats, heightened the BMD level of the femoral shaft, femoral head, and spinal column, and also raised the serum calcium and phosphorus levels of rats, while restrained apoptosis of osteocytes, elevated OCN, ALP, BGLAP, and Collα1 expression and declined ACP5, CTSK, NTX-1, CTX-1, and MMP9 expression in rats. Conclusion This study suggested that upregulating miR-410 or downregulating Wnt-11 increases osteoblasts and reduces osteoclasts to alleviate the occurrence of ONFH. Thus, miR-410 may serve as a potential target for the treatment of ONFH.